Selective degradation of hyperphosphorylated tau by proteolysis-targeting chimeras ameliorates cognitive function in Alzheimer’s disease model mice - Yao, Dongping; Li, Ting; Yu, Lu; Hu, Mingxing; He, Ye; Zhang, Ruiming; Wu, Junjie; Li, Shuoyuan; Kuang, Weihong; Yang, Xifei; Liu, Gongping; Xie, Yongmei (Frontiers in Pharmacology, 2024)
Alzheimer's disease (AD) is one of the most common chronic neurodegenerative diseases.Hyperphosphorylated tau plays an indispensable role in neuronal dysfunction and synaptic damage in AD. Proteolysis-targeting chimeras (PROTACs) are a novel type of chimeric molecule that can degrade target proteins by inducing their polyubiquitination. This approach has shown promise for reducing tau protein levels, which is a potential therapeutic target for AD. Compared with traditional drug therapies, the use of PROTACs to reduce tau levels may offer a more specific and efficient strategy for treating AD, with fewer side effects. In the present study, we designed and synthesized a series of small-molecule PROTACs to knock down tau protein. Of these, compound C8 was able to lower both total and phosphorylated tau levels in HEK293 cells with stable expression of wild-type full-length human tau (termed HEK293-htau) and htau-overexpressed mice. Western blot findings indicated that C8 degraded tau protein through the ubiquitin-proteasome system in a time-dependent manner. In htau-overexpressed mice, the results of both the novel object recognition and Morris water maze tests revealed that C8 markedly improved cognitive function. Together, our findings suggest that the use of the small-molecule PROTAC C8 to degrade phosphorylated tau may be a promising therapeutic strategy for AD.